A bio rector - Shamsudin, Rosnah; Samsu Baharuddin, Azhari; Ramli, Norilyana (2014)
The present invention relates to a system for use in a solid state fermentation (SSF), submerged state fermentation (SMF) and drying process. Generally, the present invention relates to a bio reactor comprising: a tank (100) having a mixer (101) and a perforated plate (103) inside; a cover (200) covering the tank, the cover (200) having a probe hole (201) and a filtered air outlet (203); a dosing pump; a motor (400) to drive the mixer (101); a thermocouple (500); a control panel (600) to regulate parameters such as temperature, pH and dosage, having a switch (601), a mixer speed controller (603); and a sampling port (700) to provide a flow out passage for biomass and extraction solution; and a filtered air inlet (800) located under the tank (100); characterized in that a heating mechanism is incorporated in the reactor to provide heating function of the reactor to the sample.